A slot reallocation model for containership schedule adjustment. Issue 1 (2nd January 2016) - Lu, Hua-An; Mu, Wen-Hung
Abstract : Ship slot capacity is the main sale resource of container shipping lines. However, shipping lines often encounter situations, such as serious ship delays, that require adjustments of shipping schedules, causing the original delivery plans of some consignments to be altered. This study proposes an integer programming model for slot reallocation planning, based on a given adjusted schedule. Decisions regarding empty container repositioning are also examined. This model aims to maximise a company's benefits from deliveries of consignments and movements of empty containers. Available slots are subject to port rotation changes, allowable port handlings and ship capacity. A case study of a deep ocean loop demonstrates optimal slot reallocation, and empty container repositioning is used for illustrative purposes. The reallocation characteristics due to benefit items and the model's applicability to large-scale examples are discussed.